2001
DOI: 10.1099/00221287-147-11-2943
|View full text |Cite
|
Sign up to set email alerts
|

Volatile antimicrobials from Muscodor albus, a novel endophytic fungus

Abstract: Muscodor albus is a recently described endophytic fungus obtained from small limbs of Cinnamomum zeylanicum (cinnamon tree). This xylariaceaous fungus effectively inhibits and kills certain other fungi, and bacteria, by virtue of a mixture of volatile compounds that it produces. The majority of these compounds were identified by gas chromatography/mass spectrometry and then made into an artificial mixture that mimicked the antibiotic effects of the mixture of volatile compounds given off by the fungus. Each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
435
2
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 455 publications
(457 citation statements)
references
References 15 publications
10
435
2
10
Order By: Relevance
“…which has inhibitory effect towards Pythium ultimum and Verticillum dahliae (Stinson et al, 2003). Butyrolactone was also produced by Gliocladium roseum (Strobel et al, 2001; and in Aspegillus terreus and has shown inhibitory effect towards the pathogen Botrytis cinerea (Cazar et al, 2005). Other volatile compounds such as α-phellandrene, acetic acid pentyl ester and 2-acetyl-5-methylfuran, have also been detected in Penicillium roqueforti (Jelen, 2002), Sordoria fimricola (Wihlborg et al, 2008) and Aspergillus fumigatu (Frisvad et al, 2009), respectively, but their antifungal properties are not well-established.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…which has inhibitory effect towards Pythium ultimum and Verticillum dahliae (Stinson et al, 2003). Butyrolactone was also produced by Gliocladium roseum (Strobel et al, 2001; and in Aspegillus terreus and has shown inhibitory effect towards the pathogen Botrytis cinerea (Cazar et al, 2005). Other volatile compounds such as α-phellandrene, acetic acid pentyl ester and 2-acetyl-5-methylfuran, have also been detected in Penicillium roqueforti (Jelen, 2002), Sordoria fimricola (Wihlborg et al, 2008) and Aspergillus fumigatu (Frisvad et al, 2009), respectively, but their antifungal properties are not well-established.…”
Section: Discussionmentioning
confidence: 96%
“…For control, volatile compounds were collected from the headspace of a non-inoculated agar plate. Identification of the volatile compounds was performed by comparing with the National Institute of Standards and Technology (NIST) database on the mass spectrometer (Strobel et al, 2001;Ting et al, 2007;Trivedi et al, 2008;Wan et al, 2008). The GCMS analysis was repeated once.…”
Section: Detection Of Volatile Compounds Producedmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, volatile compounds with inhibitory effects on a range of micro-organisms were discovered in endophytic species of Muscodor and Gliocladium (Strobel et al 2001;Stinson et al 2003). Generally, volatile compounds are better known as signal transmitters in intra-and interspecific communication, and are important for pollinator attraction in many higher plants (Raguso 2001 Figure 1.…”
Section: Discussionmentioning
confidence: 99%